Bias Cahaya: Paradoks Pemberdayaan Masyarakat Pada Difabel Netra di Kota Banjarbaru - Cherry Rabiullan Sari; Ismar Hamid (Huma: Jurnal Sosiologi, 2023)
Yayasan Kesejahteraan Tunanetra Nusantara and the Kompleks Disabilitas Banjarbaru are implementing empowerment programs for the visually impaired community in Banjarbaru City. This study aims to analyze the strategic approaches applied and the successes achieved by both institutions. This research uses a qualitative approach with a case study research design in two different locations. Data collection techniques include participant observation, in-depth interviews, and documentation. The results show that the empowerment programs for the visually impaired community from both institutions have not reached an ideal level of empowerment. The strategic approaches applied by both institutions include enabling and empowering approaches, while protecting approaches are not yet evident. Enabling or fostering an empowered climate is done through the provision of literacy spaces, information dissemination, and partnerships with the government and private sectors. Empowering activities are carried out through coaching and training in production and packaging, human resources, and technology. The empowerment programs carried out by both institutions have been able to increase the confidence and skills of visually impaired people to be self-reliant, which has resulted in increased income for some of those who have been empowered. However, protective efforts are not yet evident due to the unequal business competition that exists in both institutions. The approach used by YKTN and Pertuni has not always been able to improve the quality of life for blind people, but instead has made them lazy to make better use of themselves. The attitude of charity given by the community to the blind has made most of them more comfortable living on the streets by continuing to beg. Thus, there was a paradox of empowerment in the city of Banjarbaru.